Light Scattering by Optically Soft Particles Theory and Applications - Sharma, Subodh K.; Somerford, David J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
The present monograph deals with a particular class of approximation methods in the context of light scattering by small particles. This class of approximations has been termed as eikonal or soft particle approximations. The eikonal approximation was studied extensively in the potential scattering and then adopted in optical scattering problems. In this context, the eikonal and other soft particle approximations pertain to scatterers whose relative refractive index compared to surrounding medium is close to unity. The study of these approximations is very important because soft particles occur abundantly in nature. For example, the particles that occur in ocean optics, biomedical optics, atmospheric optics and in many industrial applications can be classified as soft particles. This book was written in recognition of the long-standing and current interest in the field of scattering approximations for soft particles. It should prove to be a useful addition for researchers in the field of light scattering.
The eikonal approximation in non-relativistic potential scattering -- Eikonal approximation in optical scattering -- Other soft-particle approximations -- Applications of eikonal-type approximations.
Keywords: Physics; Geophysics; Quantum optics; Amorphous substances; Complex fluids; Optics; Optoelectronics; Plasmons (Physics).; Ecotoxicology; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Geophysics/Geodesy.; Ecotoxicology; Soft and Granular Matter, Complex Fluids and Microfluidics; Quantum Optics; Electronic books